2020
DOI: 10.1785/0120200028
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Skills of Elastic Coulomb Rate-and-State Aftershock Forecasts during the 2019 Ridgecrest, California, Earthquake Sequence

Abstract: Operational earthquake forecasting protocols commonly use statistical models for their recognized ease of implementation and robustness in describing the short-term spatiotemporal patterns of triggered seismicity. However, recent advances on physics-based aftershock forecasting reveal comparable performance to the standard statistical counterparts with significantly improved predictive skills when fault and stress-field heterogeneities are considered. Here, we perform a pseudoprospective forecasting experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
2
30
0
Order By: Relevance
“…While the background conditions and their impacts on triggering may be incompletely known and impractical to incorporate into modeling, the performance of physical models can be improved through the incorporation of ETAS-like features in spatial forecasts. Mancini et al ( , 2020 have shown, for example, that modeling secondary triggering from aftershocks in CRS models can improve their forecast performance relative to CRS models with only the mainshock triggering and can achieve performance comparable to ETAS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While the background conditions and their impacts on triggering may be incompletely known and impractical to incorporate into modeling, the performance of physical models can be improved through the incorporation of ETAS-like features in spatial forecasts. Mancini et al ( , 2020 have shown, for example, that modeling secondary triggering from aftershocks in CRS models can improve their forecast performance relative to CRS models with only the mainshock triggering and can achieve performance comparable to ETAS.…”
Section: Discussionmentioning
confidence: 99%
“…Some CRS models have already been developed that include spatial variations in the modeled receiver fault orientation, which improves their performance (e.g. Mancini et al., 2019, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations